On the annihilation of dislocation dipoles in metals - Hao Wang (AIMS Materials Science, 2017)
During plastic deformation, there is a wealth of dislocation reactions, in which dislocation dipoles may play an important role. In this review, first, the history of dislocation dipole annihilation is revisited. Then, recent progresses in elucidating the atomic-scale processes during dipole annihilation are presented with examples from representative systems. Last, the consequence of dipole annihilation, as well as experimental verifications are introduced.